Sluggish exports in advanced economies: How much is due to demand? - Louis Morel (Bank of Canada, 2015)
Exports in advanced economies have been relatively sluggish since 2011, growing at a much slower pace than observed before the global financial crisis. In this paper, export-demand equations for a panel of 18 countries in the Organisation for Economic Co-operation and Development (OECD) are estimated in order to assess whether this sluggishness can be attributed to weak foreign demand. Over half of the slowdown in advanced-economy export growth since 2011 (relative to the pre-crisis trend) can be explained by weak global demand growth. More specifically, exports in advanced economies have been restrained by the weakness of global investment, a trade-intensive demand component and weak demand out of Europe, a region that accounts for about 40 per cent of the demand for advanced-economy exports. Weak foreign demand cannot explain all of the weakness in aggregate OECD exports since 2011, suggesting that other factors have also played a role. – – Depuis 2011, la croissance des exportations des économies avancées a été relativement faible, nettement inférieure à celle observée avant la crise financière mondiale. Dans cette étude, l'auteur estime des équations de demande d'exportations pour un groupe de 18 pays membres de l'Organisation de coopération et de développement économiques (OCDE) en vue de déterminer si cette faiblesse est imputable à l'atonie de la demande étrangère. Plus de la moitié du ralentissement de la croissance des exportations des économies avancées enregistré depuis 2011 (relativement à leur progression tendancielle d'avant la crise) peut s'expliquer par la croissance timide de la demande mondiale. Plus particulièrement, les exportations des économies avancées ont été freinées par la faiblesse de l'investissement mondial, composante de la demande fortement dépendante des échanges, et par une demande anémique en Europe, région qui compte pour environ 40% de la demande d'exportations des économies avancées. La demande étrangère atone n'explique toutefois pas à elle seule la faiblesse des exportations globales des membres de l'OCDE constatée depuis 2011 : d'autres facteurs auraient joué un rôle.
Keywords: F1; F4; 330; International topics; Recent economic and financial developments; Questions internationals; Évolution économique et financière récente